2000
DOI: 10.1007/s004490000218
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing excretive production of human epidermal growth factor (hEGF) with recombinant Escherichia coli K12 system

Abstract: Human epidermal growth factor (hEGF) was expressed and excreted into culture medium in an excretory recombinant Escherichia coli system. Conditions for the production of hEGF in this system were investigated. Results showed that the slight reduction of promoter strength improved the stability of plasmid and the production of hEGF in this recombinant system. One favorable MMBL medium for hEGF production was formulated by evaluating the effects of medium components, ampicilin addition and pH. hEGF production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Interferon alpha 2 and 6 were secreted across the cytoplasmic membrane into the periplasmic space of E. coli when the mature protein was fused to the signal peptide of OmpA, a major outer membrane protein of E. coli [10,11]. Similarly, the expressed hEGF could be secreted into the medium quickly and efficiently, because of its lower molecular weight [12].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon alpha 2 and 6 were secreted across the cytoplasmic membrane into the periplasmic space of E. coli when the mature protein was fused to the signal peptide of OmpA, a major outer membrane protein of E. coli [10,11]. Similarly, the expressed hEGF could be secreted into the medium quickly and efficiently, because of its lower molecular weight [12].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher temperatures might increase the action of host proteases by recognizing the protein conformation [44]. In contrast, a temperature higher than 30 °C was more favourable for some recombinant proteins [45,46]. This might be due to the nature of stability of a particular protein towards the temperature changes during cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the lower amounts of nitrogen and carbon sources in M9 medium decreased the cell density and CGTase expression, which led to a low level of excretion. Zhinan et al [37] showed that 2 × YT was the best medium for human epidermal growth factor (hEGF) production compared with 14 other media. In studies conducted by Low et al [38] and Kushoo et al [39], TB medium was chosen for further evaluation because the richness of this medium significantly enhances protein expression.…”
Section: Effect Of the Medium On Immobilized And Free Cellsmentioning
confidence: 99%